Access to credit, natural disasters, and relationship lending - Berg, Gunhild; Schrader, Jan (Journal of Financial Intermediation, 2012)
This paper analyzes the effect of unpredictable aggregate shocks on loan demand and access to credit by combining client-level information from an Ecuadorian microfinance institution with geophysical data on natural disasters, more specifically volcanic eruptions. The results of this ‘natural experiment’ show that while credit demand increases due to volcanic activity, access to credit is restricted. Yet, we also find that bank-borrower relationships can lower these lending restrictions and that clients who are known to the institution are about equally likely to receive loans after volcanic eruptions occurred.